E NOW TEACHER? WHAT WE MAKE AHEAD OF THE PRECONCEPTION OF THE DISCRIMINATION AND THE EXCLUSION IN THE PERTAINING TO SCHOOL PHYSICAL EDUCATION. (Fiep Bulletin - online, 2014)
Now as teacher, which would be my action and reactions ahead of the preconception situations, discrimination and exclusion in my lessons? And which would be these situations. It is from these questions that this research appears. Therefore in the professors we work in a place where the cultural diversity of the pupils is great e can generate conflicts. So that these conflicts did not emerge of explosive form, I tried to carry through my lessons, wasting concepts daily pay - established that they could generate preconceptions and if to reflect in scenes of discrimination and exclusion. It is not this that the professors want in its lessons and also he was not what I wanted in mine. I do not know if I was successful in my interventions, but at least I tried, I did not close the eyes and I left that the situations occurred freely.
Keywords: Preconception; discrimination; Pertaining to School Physical Education